Operation Risk Assessment of Urban Dense Cable Passageway Based on Fuzzy-Analytic Hierarchy Process - Yongjie Nie; Daoyuan Chen; Shuai Zheng; Xiaowei Xu; Xilian Wang; Zhensheng Wu (Applied Sciences)
With the acceleration of urbanization, the development and utilization of urban underground spaces are becoming increasingly frequent, and the potential risks in the operation of urban dense cable passage may pose a major threat to the security of the urban power supply. Therefore, a risk assessment method for urban dense cable passage operation based on a fuzzy-analytic hierarchy process is proposed. Firstly, the operation risk parameters of urban dense cable channels are analyzed in detail. Secondly, the weight of each index is calculated based on the analytic hierarchy process to determine the importance of each index in the risk assessment. Then, according to the membership degree of each index, the fuzzy relationship matrix is constructed to describe the relationship between each index and the risk level, and the comprehensive risk level of the cable channel is obtained through the matrix operation. Finally, taking the actual operation of an urban dense cable channel in a certain area of the China Southern Power Grid as the research object, the safety of its operation is comprehensively evaluated, and the effectiveness of the fuzzy-analytic hierarchy process in the operation risk assessment of the urban dense cable channel is verified. Corresponding risk control measures and suggestions are proposed according to the evaluation results.